New Challenges for Socio-Cyber-Physical Systems Management - Vladimir BUDANOV; Irina ASEEVA; Vladimir ARSHINOV; Anna MAYAKOVA (Communications of International Proceedings, 2021)
The convergence of biological and technical objects and systems in modern production, everyday life and cultural practices leads to the need for the formation and management of the socio-technical landscapes of civilization. There arise problems of optimal mutual coexistence of various components of the information society, which are being built at the present stage in the form of various socio-cyber-physical systems. Penetrating generally in all spheres of society, they undoubtedly create new points for the growth of society, but, at the same time, provoke new risks and threats for the adequate management of the modern socio-technical landscape.
Keywords: Socio-Technical Landscape; Hybrid Systems; Socio-Cyber-Physical Systems; Risks; Digital Distance Education.